Major risks to aquatic biotic condition in a Neotropical Savanna River basin. (4th May 2021) - Martins, Isabela; Macedo, Diego Rodrigues; Hughes, Robert Mason; Callisto, Marcos
Abstract: Conditions in freshwater ecosystems are responsible for maintaining biodiversity and other ecosystem services. Identifying and understanding how anthropogenic disturbances affect biotic conditions are important steps in rehabilitating and protecting environmental quality. The relative risk, relative extent, and attributable risk approaches are used to determine ecosystem conditions in ecological monitoring programs conducted across large spatial extents. Our study was conducted in the Pandeiros River basin, which is a protected area in Minas Gerais, Brazil, that contains 233 km of mapped streams that were perennial and accessible. Field sampling was conducted in the dry period (April and June 2016) at 40 randomly selected sites. Ten multimetric indices (MMIs), previously determined to be sensitive in this river basin, were calculated. All the physical habitat disturbance metrics were significantly correlated with the MMIs. The risk of finding poor MMI scores was 1.6–1.7 times higher at sites with a high integrated disturbance index (IDI) or local disturbance index (LDI) score. Pasture was the most extensive disturbance, affecting 40.8% of the stream length, followed by 40.1% for low bed stability, 29% for fine substrates (<16 mm), 24.4% for high IDI scores, and 21.7% for high LDI scores. This is useful to know for five reasons: (1) standardized MMIs can assess environmental quality. (2) MMIs clarify that both catchment and local disturbances may represent serious risks to aquatic assemblages. (3) MMIs indicate which disturbances represent the most risk by comparing MMI scores against disturbance scores. (4) MMI risk assessments facilitate choosing the most appropriate mitigation actions. (5) Our results suggest environmental conservation actions for similar river basins.